Association of hypertriglyceridemic waist-to-height ratio and its dynamic status with risk of type 2 diabetes mellitus: The Rural Chinese Cohort Study. (September 2021) - Qie, Ranran; Li, Quanman; Zhao, Yang; Han, Minghui; Liu, Dechen; Guo, Chunmei; Zhou, Qionggui; Tian, Gang; Huang, Shengbing; Wu, Xiaoyan; Zhang, Yanyan; Qin, Pei; et al.
Highlights: Our analysis may close the gap in knowledge about the association of HWHtR with T2DM. Participants with baseline NTHWH/HTNWH and HTHWH showed a increased risk of T2DM. We observed a significant association of the HWHtR phenotype's change with T2DM. Abstract: Aims: To evaluate the risk of type 2 diabetes mellitus (T2DM) in a prospective study with hypertriglyceridemic waist-to-height ratio (HWHtR) and its dynamic status. Methods: We collected data for 12, 248 participants ≥18 years in this study. Cox's proportional-hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for T2DM risk by baseline HWHtR. Multiple logistic regression analysis was used to estimate odds ratios (ORs) and 95% CIs for T2DM risk by transformation in HWHtR. Results: We identified 839 T2DM cases during a median follow-up of 5.92 years. Compared with normal TG level and normal WHtR, T2DM risk was increased with high TG level and high WHtR (aHR 2.04, 95% CI 1.49–2.79). Similar results were observed in subgroup analyses by sex and age. During follow-up, T2DM risk was increased with stable high TG level and high WHtR (aOR 4.45, 95% CI 2.76–7.17) compared with stable normal TG level and normal WHtR. The results above were robust in sensitivity analyses. Conclusions: HWHtR phenotype and its dynamic status were associated with risk of T2DM. Our study suggests that primary prevention and avoiding the appearance of the HWHtR phenotype in the rural Chinese population may reduce the T2DM risk.